2002
DOI: 10.1001/archopht.120.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysregulation in the Choroid of Subjects With Acral Vasospasm

Abstract: To assess the relationship between ocular perfusion pressure and blood flow in the choroid in subjects with acral vasospasm. Patients and Methods: Twenty otherwise healthy subjects with acral vascular dysregulation and 55 agematched nonvasospastic healthy volunteers were recruited. After a 20-minute rest in a sitting position, intraocular pressure and choroidal blood flow were determined by means of applanation tonometry and choroidal laser Doppler flowmetry, respectively. The laser Doppler flowmetry variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
(56 reference statements)
0
27
0
3
Order By: Relevance
“…23 In contrast, a different study, similar to our results, reported a decrease in the choroidal thickness in migraine patients, especially five of the patients during attack, according to the control group, which supports our suggestion of decreased blood flow according to the vasogenic theory of migraine. 18 It is also reported that the patients with migraine often suffer from vascular dysregulation involving the choroid 24 and this may be in relation with the choroidal thickness changes in migraine patients. Our study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…23 In contrast, a different study, similar to our results, reported a decrease in the choroidal thickness in migraine patients, especially five of the patients during attack, according to the control group, which supports our suggestion of decreased blood flow according to the vasogenic theory of migraine. 18 It is also reported that the patients with migraine often suffer from vascular dysregulation involving the choroid 24 and this may be in relation with the choroidal thickness changes in migraine patients. Our study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of parallel changes in peripheral blood flow (fingers) and visual field in vasospastic patients [16] led to the definition of an entity called "presumed ocular vasospastic syndrome" [7]. Additional studies led further support to the idea that some parallelisms in ocular and digital blood flow exist [11,15] and that the presumed ocular vasospastic syndrome is associated with a lack of blood flow autoregulation [12,14,18]. Ocular vasospastic phenomena have also been observed directly in patients with unstable primary angina [2] and with migraine [24].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an abnormal reaction of the choroidal blood flow was found in patients with progressive glaucoma during the isometric hand-grip test [49 • ], a test used to measure the sympathetic function in a well-studied reflex pathway [50]. In addition, choroidal blood flow in the foveal choriocapillaris correlates with ocular perfusion pressure in subjects with vasospasm but not in normal controls [51]. Gherghel et al [52 • ] found that glaucoma patients and control subjects differ with respect to their systemic and ocular vascular responses to warm and cold stimuli.…”
Section: Vascular Dysregulationmentioning
confidence: 99%